An Analysis of Entry Modes In The Chinese Car Industry - Hu, Liu (2007)
Over the past decades, economic globalization is irresistible in the present world. In 2001, China accessed into World Trade Organization (WTO), forcing Chinese companies to reposition them to meet the challenges from oversea companies. Especially, Chinese car industry will suffer a lot. To serve customers outside the existing domestic market, a firm needs to choose the best mode of entry into the foreign industry. The choice of the appropriate entry mode for a particular foreign market is of critical importance for a firm conducting its business in the foreign market and has been identified as a frontier issue in international marketing.